Congenital hydrocephalus secondary to Walker-Warburg syndrome identified on the Manitoba Neonatal Screening Programme for Duchenne muscular dystrophy. Issue 8 (August 1992) - Greenberg, C R; Jacobs, H K; Nylen, T E; Gibb, M; Chodirker, B N; Moffatt, M; Lacson, A; Halliday, W; Bernier, F; el-Husseini, A
Abstract : This report describes our first experience with a clinically important true false positive neonatal screening test for Duchenne muscular dystrophy (DMD). Neonatal screening for DMD began as a pilot programme in Manitoba on 1 January 1986 by analysis of creatine kinase (CK) activity in dried filter paper blood spots. To date, all except two males with positive initial and follow up neonatal CK screening tests were subsequently diagnosed as having DMD. Of these two, one was a newborn male with congenital hydrocephalus whose positive DMD screening test led to the identification of an associated congenital myopathy and confirmation of the diagnosis of Walker-Warburg syndrome.